Improving the self-imaging in multimode interference (MMI) couplers - Yin, Rui (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
A new structure is firstly proposed to be used as the multimode interference (MMI) region in this paper. For comparison with conventional MMI region, two extra layers with thin thickness and lower index beside the core layer are introduced to increase the difference of propagation constant between the first two modes. Meanwhile, high order modes are not affected so much. Thus the propagation constant errors of the guided modes are decreased and better self-imaging is realized. The designing process is also given in this paper. This new structure can be applied to any kind of M×N MMI couplers. By incorporating this new structure, an MMI based power splitter is 1/6 shorter and contrast of MMI optical switch is 10 dB higher according to the results of exact mode analysis.
Optica Applicata, Vol. 41, 2011, Nr 3, s. 679-685
Keywords: optyka; integrated optics; multimode interference (MMI); self-imaging